Hollow CdS (at) NiS (at) PdS catalyst for preparing hydrogen through photocatalytic water decomposition

By supporting NiS and PdS cocatalysts on the hollow CdS support, the CdS@NiS@PdS composite catalyst is formed, which solves the photocorrosion and stability problems of a single CdS catalyst during photocatalytic water decomposition to prepare hydrogen, and significantly improves the photocatalytic hydrogen evolution activity and stability.

CN119524883AInactive Publication Date: 2025-02-28XIAMEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411859431.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The single CdS catalyst has severe photocorrosion and poor stability when photocatalyzed water decomposition to prepare hydrogen, which limits its photocatalytic activity and practical application.

Method used

By supporting NiS and PdS cocatalysts on the hollow CdS support, the CdS@NiS@PdS composite catalyst is formed, and the photocatalytic decomposition of water in the catalyst is used to improve the performance of hydrogen produced by photocatalytic decomposition of water in the catalyst.

Benefits of technology

The hollow CdS@NiS@PdS catalyst significantly improves the photocatalytic hydrogen evolution activity, with a hydrogen evolution rate of 32.63 mmol·g-1·h-1, which is 28.9 times that of pure hollow CdS performance, and has excellent stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to the technical field of photocatalytic hydrogen production catalysts, and discloses a plurality of catalysts for preparing hydrogen through photocatalytic water decomposition, the plurality of catalysts can be respectively represented by a formula CdS (at) NiS (at) PdS, a formula CdS (at) NiS or a formula CdS (at) PdS, meanwhile, the invention also discloses a preparation method of the catalyst and an application of the catalyst in photocatalytic hydrogen production, the catalyst has good reaction performance of photocatalytic decomposition of water to prepare hydrogen, NiS and PdS are loaded on the surface of CdS as cocatalysts, and the photocatalytic performance and the stability can be obviously improved by the pure hollow CdS design; the method has good application potential in promotion of industrial development of direct large-scale hydrogen preparation by using solar energy, and the synthesis method is simple, easy to operate, good in repeatability and easy for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and specifically discloses a hollow CdS@NiS@PdS catalyst for preparing hydrogen by photocatalytic water decomposition. Background Art

[0002] The increasing consumption of traditional fossil energy has caused problems such as extreme weather and energy crisis, and the development of alternative renewable energy is urgent. Hydrogen energy has the characteristics of clean and low-carbon properties, high energy density, strong storability and transportability, and is expected to replace fossil fuels as the mainstream energy form. However, traditional thermal catalytic hydrogen production requires a large amount of fossil fuels, is costly and emits a lot of greenhouse gases. The new photocatalytic hydrogen production technology can directly convert solar energy into hydrogen energy. It is a low-cost, green and low-carbon sustainable hydrogen production method that can achieve large-scale production of hydrogen energy, which is conducive to promoting the transformation of the energy structure to a low-carbon and clean one, and has broad application prospects.

[0003] Common photocatalytic materials include metal sulfides, metal oxides, metal nitrides, etc. Among them, metal sulfides have suitable energy band positions, so they have excellent charge separation efficiency and low redox potential and are highly favored. Cadmium sulfide (CdS) has always been one of the ideal materials for photocatalytic hydrogen production from water due to its low cost, suitable band gap and good visible light response. However, the single CdS catalyst has severe photocorrosion and poor stability, which to some extent limits its photocatalytic activity and practical application.

[0004] The hollow structure of CdS increases the overall surface area, exposes more active sites, and enhances the efficiency of light utilization. Its performance is also better than that of conventional CdS. Constructing a co-catalyst is an effective way to enhance the efficiency of hydrogen evolution. Modifying the co-catalyst on the surface of CdS can trigger the re-balance of electrons inside the two materials due to the difference in their Fermi levels, promoting the surface separation of charge carriers. Density functional theory (DFT) calculation results show that NiS as an electron co-catalyst can not only promote H 2 The dissociation of O molecules on the catalyst surface accelerates the surface reaction kinetics and greatly improves the hydrogen production activity. At the same time, the hole-promoting catalyst PdS can accelerate the oxidation end reaction kinetics, thereby promoting the coordination of redox rates and improving the catalytic efficiency of the overall catalyst system.

[0005] Based on this, it is necessary to provide a preparation method and application of a composite catalytic material in which NiS and PdS co-catalysts are loaded on hollow CdS to improve its catalytic activity and stability. Summary of the invention

[0006] In view of the problems existing in the prior art, the first aspect of the present invention provides a method for preparing a hollow CdS carrier, comprising: Step 1: Alcohol, water and ammonia water are mixed to form a first mixed system, hexyl orthosilicate is added to the alcohol to form a second mixed system, the first mixed system and the second mixed system are combined, separated and dried to obtain SiO 2 ball; Step 2: Prepare SiO from step 1 2 The ball was put into water, and then sodium citrate, cadmium acetate, thiourea and ammonia water were added in sequence, mixed at 50-120°C, the solid was separated and dried to obtain SiO 2 @CdS; Step 3: SiO 2 @CdS is mixed with sodium hydroxide solution, mixed at 60-130°C, cooled, the solid is separated, and dried to obtain a hollow CdS carrier.

[0007] In some specific embodiments of the first aspect of the present invention, in step 1, the volume ratio of water, alcohol and aqueous ammonia is (20-29): (12-18): (8-12).

[0008] In some specific embodiments of the first aspect of the present invention, in step 1, the mass fraction of ammonia in the ammonia water is 20-35%.

[0009] In some specific embodiments of the first aspect of the present invention, in step 1, the method of adding hexyl orthosilicate to alcohol is to add 2 to 5 parts by volume of hexyl orthosilicate to 40 to 50 parts by volume of alcohol.

[0010] In some specific embodiments of the first aspect of the present invention, in step 2, the mass fraction of the ammonia water is 28%.

[0011] In some specific embodiments of the first aspect of the present invention, in step 2, the SiO 2 Ball 1~2g.

[0012] In some specific embodiments of the first aspect of the present invention, in step 2, the molar amount of sodium citrate added per 1L of water is 10-30 mmol.

[0013] In some specific embodiments of the first aspect of the present invention, in step 2, the molar amount of cadmium acetate fed per 1L of water is 10-30 mmol.

[0014] In some specific embodiments of the first aspect of the present invention, in step 2, the molar amount of thiourea fed per 1 L of water is 30-50 mmol.

[0015] In some specific embodiments of the first aspect of the present invention, in step 2, the volume of ammonia water added per 1L of water is 1-3mL.

[0016] In some specific embodiments of the first aspect of the present invention, in step 3, the SiO 2 @CdS input amount is 3-6 g, and the molar concentration of the sodium hydroxide aqueous solution is 0.8-1.2 mol·L -1 .

[0017] The second aspect of the present invention provides a hollow CdS carrier prepared by the method described in any embodiment of the first aspect.

[0018] The third aspect of the present invention provides a catalyst represented by the formula CdS@x%NiS@y%PdS, wherein the x% is the mass fraction of NiS in the hollow CdS carrier, the x is selected from 0.5 to 2, the y% is the mass fraction of PdS in the hollow CdS carrier, and the y is selected from 0.1 to 2; The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

[0019] The fourth aspect of the present invention provides a method for preparing a catalyst represented by the formula CdS@x%NiS@y%PdS described in the third aspect, comprising: S1: adding the hollow CdS carrier of claim 3 to an organic solvent, then adding an aqueous solution of a nickel salt and an aqueous solution of a sulfide salt, mixing, separating a solid, and drying; S2: Add an aqueous solution of palladium salt and sulfide salt to the dried solid, mix well, separate the solid, and dry to obtain the catalyst represented by the formula CdS@x%NiS@y%PdS as claimed in claim 4, wherein x% is the mass fraction of NiS in the hollow CdS carrier, and x is selected from 0.5 to 2; y% is the mass fraction of PdS in the hollow CdS carrier, and y is selected from 0.1 to 2.

[0020] In some specific embodiments of the fourth aspect, in step S1, the molar amount of nickel salt added per 1 L of organic solution is 0.09-0.12 mmol.

[0021] In some specific embodiments of the fourth aspect, the nickel salt is selected from any one or a combination of nickel chloride, nickel sulfate, nickel nitrate, and nickel acetate, and / or, in step S1, 0.09-0.12 mmol of sulfide salt is added per 1 L of organic solvent.

[0022] In some specific embodiments of the fourth aspect, the sulfide salt in step S1 is selected from any one or a combination of sodium sulfide and potassium sulfide. In some specific embodiments of the fourth aspect, in the step S2, the mass of palladium salt fed into every 1 L of organic solution is 29.5-118 mg.

[0023] In some specific embodiments of the fourth aspect, in the step S2, 0.09-0.36 mmol of sulfide salt is added per 1 L of organic solvent, and / or, in the step S2, the sulfide salt is selected from any one or a combination of sodium sulfide and potassium sulfide, A fifth aspect of the present invention is a catalyst prepared by any method embodiment of the fourth aspect.

[0024] In a sixth aspect, the present invention provides a catalyst represented by the formula CdS@x%NiS, wherein x% is the mass fraction of NiS in the hollow CdS carrier, and x is selected from 0.5 to 5. The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

[0025] In a seventh aspect, the present invention provides a catalyst represented by the formula CdS@y%PdS, wherein the y% is the mass fraction of PdS in the hollow CdS carrier, and the y is selected from 0.1 to 2. The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

[0026] The eighth aspect of the present invention provides a method for preparing the CdS@y%PdS catalyst of the seventh aspect, comprising: The hollow CdS carrier of claim 3 is added to an organic solvent, and then an aqueous nickel acetate solution and an aqueous sodium sulfide solution are added, and the solid is separated and dried to obtain a catalyst represented by the formula CdS@y%PdS.

[0027] The ninth aspect of the present invention provides an application of any catalyst of the second aspect, the third aspect, the fifth aspect, the sixth aspect, and the seventh aspect in photocatalytic hydrogen production, comprising: Add any one of the catalysts of the second aspect, the third aspect, the fifth aspect, the sixth aspect, and the seventh aspect to a mixture of water and lactic acid to form a reaction system, and irradiate the reaction system with a light source having a wavelength greater than 420 nm.

[0028] Terminology Certain embodiments of the present invention are now described in detail. The present invention is intended to cover all substitutions, modifications and equivalent technical solutions, which are all included in the scope of the present invention as defined in the claims. It should be appreciated by those skilled in the art that many methods and materials similar or equivalent to those described herein can be used to practice the present invention. The present invention is by no means limited to the methods and materials described herein. In the event that one or more of the combined documents, patents and similar materials are different from or contradictory to the present application (including but not limited to defined terms, term applications, described technologies, etc.), the present application shall prevail.

[0029] It should be further appreciated that certain features of the invention, which for clarity are described in multiple separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention, which for brevity are described in a single embodiment, may also be provided separately or in any suitable sub-combination.

[0030] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0031] In the following, all numbers disclosed herein are approximate, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% will be explicitly disclosed, where "+ / -" means plus or minus.

[0032] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.

[0033] The beneficial technical effects of the present invention are as follows: The present invention uses hollow CdS as a substrate. Compared with a solid structure, the hollow structure causes multiple reflections and scattering of light in the internal cavity, thereby enhancing the light absorption capacity of the catalyst and improving the light utilization efficiency. In addition, the hollow structure has a larger specific surface area and can provide more active sites to participate in the photocatalytic reaction. The present invention prepares a hollow CdS spherical structure, which can significantly improve the photocatalytic hydrogen evolution activity.

[0034] The hollow CdS with NiS and PdS dual promoters loaded on the surface provided by the present invention has good photocatalytic water decomposition to produce hydrogen reaction performance. In a system in which lactic acid is used as a sacrificial agent and in an argon atmosphere, a 300 W xenon lamp (λ>420 nm) with a cutoff filter is used for irradiation for 2 h, and 10 mg of photocatalyst is added for photocatalytic reaction, NiS is loaded on the surface of CdS as a promoter, and changing its mass ratio (0.5%, 1%, 3%, 5%) can improve the photocatalytic performance of CdS, wherein the composite catalyst with a loading amount of 1% (CdS@NiS) has the best hydrogen evolution performance, which is 4 times that of pure hollow CdS; if PdS is loaded on the surface of CdS@NiS, changing its mass ratio (0.1%, 0.5%, 1%, 2%) can also greatly improve the photocatalytic hydrogen evolution performance, wherein the hydrogen evolution performance is best when the loading amount is 0.5% (CdS@NiS@PdS), and the hydrogen evolution rate reaches 32.63 mmol·g -1 ·h -1 , which is 28.9 times the performance of pure hollow CdS and 38 times the performance of solid CdS. At the same time, if solid CdS is used as the substrate and 1% NiS and 1% PdS are loaded on its surface, the performance is only 2.82 mmol·g -1 ·h -1 , which is significantly lower than the performance of hollow CdS@1wt%NiS@1%wtPdS (29.28 mmol·g -1 ·h -1 ). In addition, the CdS@NiS@PdS also has excellent stability and shows good application potential in promoting the development of the industry of directly producing hydrogen on a large scale using solar energy.

[0035] The synthesis method of the invention is simple and easy to operate, has good repeatability and is easy for large-scale production.

[0036] The experiment used a common hard template method to prepare CdS with a hollow spherical structure. During the synthesis process, NiS and PdS were modified on its surface to obtain a hollow CdS@NiS@PdS bifunctional auxiliary composite catalyst, which showed high catalytic activity in the photocatalytic decomposition of water to produce hydrogen. This preparation method uses simple hard template methods, in-situ modification and other methods, and regulates the content of modified NiS and PdS to obtain a hollow CdS@NiS@PdS bifunctional dual-auxiliary catalyst with high photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 XRD spectra of hollow CdS prepared in Examples 3, 4, 5, 6, and 7 and CdS@NiS with different NiS loading amounts and CdS standard PDF cards; Figure 2XRD spectra of CdS@NiS@PdS and CdS@1% wtPdS with different PdS loadings prepared in Examples 8, 9, 10, 11, and 12 and CdS standard PDF cards; Figure 3 This is a SEM image of CdS@NiS@PdS prepared in Example 10; Figure 4 HRTEM images of CdS@1% wt NiS@1% wt PdS prepared in Example 10. (a), (b), and (c) are transmission images of CdS@1% wt NiS@1% wt PdS at different magnifications, and (d) is an EDS spectrum image; Figure 5 The hydrogen evolution performance diagram of hollow CdS prepared in Examples 3, 4, 5, 6, and 7 and CdS@NiS with different NiS loading amounts; Figure 6 This is a diagram of the hydrogen evolution performance of CdS@NiS@PdS with different PdS loading amounts prepared in Examples 5, 8, 9, 10, and 11. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present disclosure. The technical scheme of the present invention is illustrated below, and the scope of protection of the present invention includes but is not limited to the following embodiments.

[0039] Catalyst preparation Example 1 Spherical SiO 2 Preparation Take 16.25 mL of anhydrous ethanol and 9 mL of concentrated ammonia (NH 3 ·H 2 O, 28%) was mixed with 24.75 mL of deionized water to form solution A.

[0040] Disperse 4.5 mL of hexyl orthosilicate in 45.5 mL of ethanol to form solution B. Quickly pour solution B into solution A while stirring at 1100 rpm for 1 minute. Then reduce the speed to 600 rpm, stir for 2 hours, and then centrifuge and wash the SiO with water and ethanol respectively. 2 The SiO 2 .

[0041] Example 2 Spherical SiO 2 Preparation of @CdS Take 150 mg SiO 2 The mixture was suspended in 100 mL of water by ultrasonication and 1 mol·L -1 2 mL of sodium citrate aqueous solution was stirred for 10 minutes; then 1 mol·L -1 2 mL of cadmium acetate dihydrate aqueous solution was added and stirred for 20 minutes; then, 4 mL of 1 mol·L -1 2 mL of thiourea aqueous solution and 2 mL of 28% concentrated ammonia water were added. Then, the suspension was transferred to a 150 mL round-bottom flask and stirred at 80 °C in an oil bath for 3 hours. After cooling to room temperature, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain SiO 2 @CdS.

[0042] Example 3 Preparation of Hollow CdS Take 500 mg SiO 2 @CdS and 100 mL 1 mol·L -1 The sodium hydroxide aqueous solution was mixed with a 150 mL round-bottom flask and stirred at 90 °C in an oil bath for 3 hours. After cooling to room temperature, the precipitate was centrifuged and washed with water and ethanol, respectively, and dried in a vacuum oven at 60 °C overnight to obtain hollow CdS.

[0043] Example 4 Preparation of CdS@0.5wt%NiS 50 mg of hollow CdS was added to 20 mL of n-hexane, ultrasonicated and homogenized, and 0.02 mol·L -1 0.138 mL of nickel acetate tetrahydrate aqueous solution was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.138 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain a composite catalyst with a mass fraction of NiS in the hollow CdS of 0.5% (CdS@0.5wt%NiS).

[0044] Example 5 Preparation of CdS@1wt%NiS 50 mg of hollow CdS was added to 20 mL of n-hexane, ultrasonicated and homogenized, and 0.02 mol·L -1 0.275 mL of nickel acetate tetrahydrate aqueous solution was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -10.275 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%NiS.

[0045] Example 6 Preparation of CdS@2wt%NiS 50 mg of hollow CdS was added to 20 mL of n-hexane, ultrasonicated and homogenized, and 0.02 mol·L -1 0.826 mL of nickel acetate tetrahydrate aqueous solution was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.826 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@2wt%NiS.

[0046] Example 7 Preparation of CdS@5wt%NiS 50 mg of hollow CdS was added to 20 mL of n-hexane, ultrasonicated and homogenized, and 0.02 mol·L -1 1.377 mL of nickel acetate tetrahydrate aqueous solution was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 1.377 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@5wt%NiS.

[0047] Example 8 Preparation of CdS@1wt%NiS@0.1wt%PdS 50 mg CdS@1wt%NiS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 1 mg·mL -1 0.118 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.018 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%NiS@0.1% wt PdS.

[0048] Example 9 Preparation of CdS@1wt%NiS@0.5wt%PdS 50 mg CdS@1wt%NiS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 1 mg·mL-1 0.590 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.090 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%NiS@0.5wt%PdS.

[0049] Example 10 Preparation of CdS@1wt%NiS@1wt%PdS 50 mg CdS@1wt%NiS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 1 mg·mL -1 1.179 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.180 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%NiS@1wt%PdS, which was named CdS@NiS@PdS.

[0050] Example 11 Preparation of CdS@1wt%NiS@2wt%PdS 50 mg CdS@1% wt NiS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 1 mg mL -1 2.358 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.361 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%NiS@2wt%PdS.

[0051] Example 12 Preparation of CdS@1wt%PdS 50 mg of hollow CdS was added to 20 mL of n-hexane, ultrasonicated and homogenized, and 1 mg mL -1 1.179 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.180 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction was completed, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS@1wt%PdS.

[0052] Comparative Example 1 Preparation of solid CdS 266.53 mg of cadmium acetate dihydrate and 304.48 mg of thiourea were dispersed in 40 mL of ultrapure water and stirred for 30 minutes. The solution was then transferred into a 50 mL hydrothermal reactor and reacted at 160 °C for 12 hours. After the reaction, the pure CdS was centrifuged and washed with water and ethanol, respectively, and dried in a vacuum oven at 60 °C overnight to obtain CdS nanospheres.

[0053] Comparative Example 2 Preparation of solid CdS@1wt%NiS 50 mg solid CdS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 0.02 mol·L -1 0.275 mL of nickel acetate tetrahydrate aqueous solution was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.275 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain solid CdS@1wt%NiS.

[0054] Comparative Example 3 Preparation of solid CdS@1wt%NiS@1wt%PdS 50 mg solid CdS@1wt%NiS was added to 20 mL n-hexane, ultrasonicated and homogenized, and 1 mg·mL -1 1.179 mL of potassium hexachloropalladate was added and stirred at 300 rpm for 2 hours; then 0.02 mol·L -1 0.180 mL of sodium sulfide aqueous solution was added and stirring was continued for 2 hours. After the reaction, the precipitate was centrifuged and washed with water and ethanol respectively, and dried in a vacuum oven at 60 °C overnight to obtain solid CdS@1wt%NiS@1wt%PdS.

[0055] Study on Hydrogen Evolution Performance of CdS-based Catalysts Photocatalytic water decomposition to produce hydrogen performance test: 10 mg of photocatalyst was added to 9 mL of ultrapure water and 1 mL of lactic acid, loaded into a sealed tube reactor (volume: 20 mL; inner diameter: 16 mm), filled with argon and ultrasonicated for 5 min. Subsequently, visible light irradiation was performed using a 300 W xenon lamp (λ>420 nm) with a cutoff filter for 2 h. H was detected by Agilent 7890A gas chromatography. 2 Yield.

[0056] The test results show (as shown in Figures 5 and 6) that the hollow structure improves the photocatalytic hydrogen evolution performance of CdS. The hydrogen evolution performance of hollow CdS is improved after NiS is loaded. With the increase of the loading amount, the hydrogen evolution performance shows a volcano graph trend of first increasing and then decreasing. Among them, the performance is the best when the loading amount is 1%. CdS@1wt%NiS can also significantly improve the photocatalytic hydrogen evolution performance after PdS is loaded. The hydrogen evolution performance is the best when the loading amount is 0.5%, and the hydrogen evolution rate reaches 32.63 mmol·g -1 ·h -1 , which is 28.9 times the performance of pure hollow CdS. At the same time, if 1% NiS and 1% PdS are loaded on solid CdS, its performance is only 2.82mmol·g -1 ·h -1 , which is significantly lower than the performance of hollow CdS@1wt%NiS@1%wtPdS (29.28 mmol·g -1 ·h -1 ).

[0057] X-ray powder diffraction (XRD) test The catalyst prepared by the present invention was subjected to XRD test. The results shown in FIG1 and FIG2 indicate that CdS was successfully synthesized, and no obvious phase separation occurred after modification with NiS and PdS.

[0058] Scanning Electron Microscope (SEM) Testing The catalyst prepared by the present invention was subjected to SEM test. The result is shown in FIG3 , indicating that the spherical CdS was successfully synthesized, and the spherical morphology was not destroyed after modification with NiS and PdS.

[0059] High Resolution Transmission Electron Microscopy (HRTEM) Testing The microstructure and elements of the samples were characterized by high-resolution transmission electron microscopy (HRTEM) equipped with an X-ray energy dispersive spectrometer (EDS). The results are shown in Figure 4, indicating the successful synthesis of the hollow structure and the successful loading of NiS and PdS.

[0060] The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein within the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.

Claims

1. A method for preparing a hollow CdS carrier, comprising: Step 1: Alcohol, water and ammonia water are mixed to form a first mixed system, orthosilicate is added to the alcohol to form a second mixed system, the first mixed system and the second mixed system are combined, separated and dried to obtain SiO2 balls; Step 2: Take the SiO2 ball obtained in step 1, put it into water, then add sodium citrate, cadmium acetate, thiourea and ammonia water in sequence, mix at 50-120°C, separate the solid, and dry it to obtain SiO2@CdS; Step 3: Mix SiO2@CdS with sodium hydroxide solution, mix at 60-130°C, cool, separate the solid, and dry to obtain a hollow CdS carrier.

2. The preparation method according to claim 1, characterized in that: In the step 1, the volume ratio of the water, alcohol and ammonia water is (20-29): (12-18): (8-12), and / or, in the step 1, the mass fraction of ammonia in the ammonia water is 20-35%, and / or, in the step 1, the method of adding ethyl orthosilicate to the alcohol is to add 2-5 parts by volume of ethyl orthosilicate to 40-50 parts by volume of alcohol, and / or, in the step 2, the concentration of the ammonia water is, and / or, in the step 2, 1-2 g of SiO2 balls are added to every 1 L of water, and / or, in the step 2, every 1 L of water is The molar amount of sodium citrate in water is 10-30 mmol, and / or, in step 2, the molar amount of cadmium acetate in each 1 L of water is 10-30 mmol, and / or, in step 2, the molar amount of thiourea in each 1 L of water is 30-50 mmol, and / or, in step 2, the volume of ammonia water added in each 1 L of water is 1-3 mL, and / or, in step 3, the amount of SiO2@CdS added in each 1 L of sodium hydroxide aqueous solution is 3-6 g, and the molar concentration of the sodium hydroxide aqueous solution is 0.8-1.2 mol·L -1 .

3. A hollow CdS carrier prepared by the method according to any one of claims 1 or 2.

4. A catalyst represented by the formula CdS@x%NiS@y%PdS, wherein: The x% is the mass fraction of NiS in the hollow CdS carrier, and the x is selected from 0.5 to 2; the y% is the mass fraction of PdS in the hollow CdS carrier, and the y is selected from 0.1 to 2; The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

5. A method for preparing the catalyst represented by the formula CdS@x%NiS@y%PdS as claimed in claim 4, comprising: S1: adding the hollow CdS carrier of claim 3 to an organic solvent, then adding an aqueous solution of a nickel salt and an aqueous solution of a sulfide salt, mixing, separating a solid, and drying; S2: Add an aqueous solution of palladium salt and sulfide salt to the dried solid, mix well, separate the solid, and dry to obtain the catalyst represented by the formula CdS@x%NiS@y%PdS as claimed in claim 4, wherein x% is the mass fraction of NiS in the hollow CdS carrier, and x is selected from 0.5 to 2; y% is the mass fraction of PdS in the hollow CdS carrier, and y is selected from 0.1 to 2.

6. The method for preparing the catalyst according to claim 5, characterized in that: In the step S1, the molar amount of the nickel salt in each 1L of organic solution is 0.09-0.12mmol, and / or the nickel salt is selected from any one or a combination of nickel chloride, nickel sulfate, nickel nitrate, and nickel acetate, and / or, 0.09-0.12mmol of sulfide salt is added to each 1L of organic solvent in the step S1, and / or, the sulfide salt in the step S1 is selected from any one or a combination of sodium sulfide and potassium sulfide, And / or, in the step S2, the mass of palladium salt added to every 1L of organic solution is 29.5~118mg, and / or, in the step S2, 0.09~0.36mmol of sulfide salt is added to every 1L of organic solvent, and / or, in the step S2, the sulfide salt is selected from any one or a combination of sodium sulfide and potassium sulfide.

7. A catalyst obtained by the preparation method according to any one of claims 5 or 6.

8. A catalyst represented by the formula CdS@x%NiS, wherein: The x% is the mass fraction of NiS in the hollow CdS carrier, and the x is selected from 0.5 to 5. The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

9. A catalyst represented by the formula CdS@y%PdS, wherein: The y% is the mass fraction of PdS in the hollow CdS carrier, and the y is selected from 0.1 to 2. The hollow CdS carrier is prepared using the preparation method described in any one of claims 1 or 2.

10. Use of any one of the catalysts of claims 3, 4, 7, 8, and 9 in photocatalytic hydrogen production, comprising: Add any one of the catalysts of claim 3, 4, 7, 8 and 9 to a mixture of water and lactic acid to form a reaction system, and irradiate the reaction system with a light source having a wavelength greater than 420 nm.

Citation Information

Patent Citations

  • Catalyst capable of responding to visible light and being used for producing hydrogen by photocatalytic water splitting and preparation method of catalyst

    CN102861597A

  • Metallic oxide / metal sulfide hollow nanospheres as well as preparation method and application thereof

    CN104492460A

  • Preparation method and application of hollow sphere cadmium sulfide / nickel-cobalt-phosphorus heterojunction photocatalyst

    CN114011445A